Characteristics of Mesenchymal Stem Cells – New Stars in Regenerative Medicine or Unrecognized Old Fellows in Autologous Regeneration? - Schäfer, Richard (S. Karger GmbH, 2008)
SUMMARY: For years mesenchymal stem cells (MSC) have been in the focus of research in the emerging field of regenerative medicine. Due to the heterogeneity of cells with MSC-like properties their comprehensive characterization is necessary. In the following, issues of nomenclature, basic characterization, sources, sternness, and therapeutic potential of MSC are discussed, highlighting some aspects in the rapidly expanding field of MSC research.